Taking leadership fashions seriously as a vehicle for leadership learning. Issue 3 (July 2022) - Guthey, Eric; Ferry, Nicole Capriel; Remke, Robyn
Popularized and commercialized leadership ideas are often criticized as mere fashions that dumb down leadership discourse, research, and learning. By contrast, we take leadership fashions seriously as an important vehicle for individual and collective leadership learning. We extend the neo-institutional theory of management fashions to define leadership fashions as a process that constantly reconfigures the rational norms and expectations attached to leadership, and that elevates certain approaches as the best way to fulfill those norms and expectations. Combining Weber's broad understanding of rationality with our own concept of affective rationality, we account for the many different instrumental, practical, moral, and sometimes deeply personal and emotional norms and expectations that drive the leadership fashion setting process. This approach contributes a theoretical foundation for understanding the sociological significance of leadership fashions, for exploring the leadership industries that produce and promote them, and for researching further the ways that leadership fashions and the leadership industries influence leadership research, learning, and practice.